Wood Anatomy of Indian Species of Michelia with Particular Reference of their Identification - Chauhan, Laxmi; Dayal, R. (Indian Forester, 1992)
The wood structure of eight Indian specics of Michelia have been studied in detail with a view of determining features of diagnostic value for their identification. The study indicate that various anatomical characters viz. frequency, size and shape of vessels, presence/absence of oil cells in rays and presence/absence of spirals in vessels are likely of value for their specific delimitation. A tentative key has also been given.